Inflammatory Pain and Corticosterone Response in Infant Rats: Effect of 5-HT1A Agonist Buspirone Prior to Gestational Stress - Irina P. Butkevich; Viktor A. Mikhailenko; Tat'yana R. Bagaeva; Elena A. Vershinina; Anna Maria Aloisi; Vladimir A. Otellin (Mediators of Inflammation)
Our researches have shown that gestational stress causes exacerbation of inflammatory pain in the offspring; the maternal 5-HT1A agonist buspirone before the stress prevents the adverse effect. The serotonergic system and hypothalamo-pituitary-adrenal (HPA) axis are closely interrelated. However, interrelations between inflammatory pain and the HPA axis during the hyporeactive period of the latter have not been studied. The present research demonstrates that formalin-induced pain causes a gradual and prolonged increase in plasma corticosterone level in 7-day-old male rats; twenty-four hours after injection of formalin, the basal corticosterone level still exceeds the initial basal corticosterone value. Chronic treatments of rat dams with buspirone before restraint stress during gestation normalize in the offspring pain-like behavior and induce during the acute phase in the formalin test the stronger corticosterone increase as compared to the stress hormonal elevation in animals with other prenatal treatments. Negative correlation between plasma corticosterone level and the number of flexes+shakes is revealed in buspirone+stress rats. The new data enhance the idea about relativity of the HPA axis hyporeactive period and suggest that maternal buspirone prior to stress during gestation may enhance an adaptive mechanism of the inflammatory nociceptive system in the infant male offspring through activation of the HPA axis peripheral link.